(untitled) (JURNAL KEPERAWATAN, 2018)
Abstract : The motivation to study can influenced by stress and the same condition was on the contrary stress it can affect the motivation to study but stressful which could be more profitable managed well it could be an encouragement to the motivation to study Purpose of this research is to know the Relationship between Stress and Learning Motivation of the 5th semester students of Nursing Program, Faculty of Medicine, University of Sam Ratulangi Manado. Sample of 73 respondents using total sampling technique. Design the research in this research is correlative analysis, using Cross Sectional approach and data collected from respondents by using questionnaire sheet. Results showed there’s no Relationship between Stress and Learning Motivation of the 5th semester students of Nursing Program, Faculty of Medicine, University of Sam Ratulangi Manado with p value = 0,062. Conclusion there is no Relationship between Stress and Learning Motivation of the 5th semester students of Nursing Program, Faculty of Medicine, University of Sam Ratulangi Manado. Keywords: Stress, Learning Motivation Abstrak : Motivasi belajar bisa dapat dipengaruhi oleh stres begitupun sebaliknya stres dapat mempengaruhi motivasi belajar akan tetapi stres yang bisa dikelola dengan baik bisa menjadi suatu dorongan untuk motivasi belajar. Tujuan dalam penelitian ini adalah untuk mengetahui hubungan stres dengan motivasi belajar pada mahasiswa semester V di Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi Manado. Sampel sebanyak 73 responden dengan menggunakan teknik total sampling. Desain Penelitian dalam penelitian ini yaitu analisis korelatif, dengan menggunakan pendekatan Cross Sectional dan data dikumpulkan dari responden dengan menggunakan lembar kuesioner. Hasil Penelitian menunjukan tidak adanya hubungan stres dengan motivasi belajar pada mahasiswa semester V di Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi Manado dengan nilai p= 0,062. Kesimpulan tidak terdapat hubungan stres dengan motivasi belajar semester V di Program Studi Ilmu Keperawatan Fakultas Kedokteran Universitas Sam Ratulangi Manado. Kata Kunci : Stres, Motivasi Belajar.